2023
DOI: 10.3390/v15112229
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 ORF3a-Mediated NF-κB Activation Is Not Dependent on TRAF-Binding Sequence

Brianna M. Busscher,
Henock B. Befekadu,
Zhonghua Liu
et al.

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused a global pandemic of Coronavirus Disease 2019 (COVID-19). Excessive inflammation is a hallmark of severe COVID-19, and several proteins encoded in the SARS-CoV-2 genome are capable of stimulating inflammatory pathways. Among these, the accessory protein open reading frame 3a (ORF3a) has been implicated in COVID-19 pathology. Here we investigated the roles of ORF3a in binding to TNF receptor-associated factor (TRAF) proteins and inducing nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…The ORF3a protein exhibits several well-conserved functional motifs (Figure 1A), allowing us to hypothesize about its potential functions. Notably, it contains a TNF receptor-associated factor 3 (TRAF3)-binding motif spanning aa36-40 in both SARS-CoV-1 and SARS-CoV-2 [37,38,47,55]. Interestingly, TRAF3 plays a crucial role in regulating NF-κB signaling and cell death in SARS-CoV-1.…”
Section: Structure and Unique Features Of Orf3a Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORF3a protein exhibits several well-conserved functional motifs (Figure 1A), allowing us to hypothesize about its potential functions. Notably, it contains a TNF receptor-associated factor 3 (TRAF3)-binding motif spanning aa36-40 in both SARS-CoV-1 and SARS-CoV-2 [37,38,47,55]. Interestingly, TRAF3 plays a crucial role in regulating NF-κB signaling and cell death in SARS-CoV-1.…”
Section: Structure and Unique Features Of Orf3a Proteinmentioning
confidence: 99%
“…Initial reports suggested that the interaction between ORF3a and TRAF3 through this binding site was necessary for the activation of NF-κB and the secretion of the cytokine IL-1β [37,38]. However, studies on SARS-CoV-2 indicated that deletion of this TRAF3-binding motif in the ORF3a protein did not affect its ability to induce NF-κB activation or NF-κB-mediated cytokine production [47,55]. The underlying cause of this discrepancy is presently unclear.…”
Section: Structure and Unique Features Of Orf3a Proteinmentioning
confidence: 99%